2014
DOI: 10.1111/crj.12230
|View full text |Cite
|
Sign up to set email alerts
|

Tiotropium may improve asthma symptoms and lung function in asthmatic patients with irreversible airway obstruction: the real‐life data

Abstract: Our study has suggested that, for patients with poorly controlled asthma despite of the use of ICS/LABA, the addition of tiotropium to standard care may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…An analysis of 64 patients with poor disease control despite treatment with high dose ICS/LABA showed that the introduction of tiotropium as add on therapy improved asthma control in 42.2% of cases, decreasing the number of emergency department visits and hospitalizations in 46.9% and 50.0% of cases, respectively [149]. A larger cohort involving 2,042 outpatients from United Kingdom compared the number of exacerbations (emergency visits, hospitalizations and oral corticosteroids use) and acute asthma events (antibiotic use for lower respiratory tract infections) in the year before and in the year following the prescription of tiotropium.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of 64 patients with poor disease control despite treatment with high dose ICS/LABA showed that the introduction of tiotropium as add on therapy improved asthma control in 42.2% of cases, decreasing the number of emergency department visits and hospitalizations in 46.9% and 50.0% of cases, respectively [149]. A larger cohort involving 2,042 outpatients from United Kingdom compared the number of exacerbations (emergency visits, hospitalizations and oral corticosteroids use) and acute asthma events (antibiotic use for lower respiratory tract infections) in the year before and in the year following the prescription of tiotropium.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies have confirmed that treatment with anticholinergics as an add-on to ICS or ICS+LABA improves lung function and reduces the number of exacerbations, emergency room visits, and hospitalisations (66, 67). …”
Section: Indicator 3: Long-acting Beta-agonist Use Without Concomitanmentioning
confidence: 95%
“…Findings showed that primary care physicians in the UK have been prescribing long-acting anticholinergics for the treatment of asthma since 2002, predominantly as an add-on therapy in older patients with poorly controlled asthma despite good treatment compliance, particularly in those who are current or former smokers [63]. Similarly, in a second retrospective study of real-life data from 64 patients with severe asthma in Turkey, tiotropium add-on to high-dose ICS plus LABA therapy was found to significantly improve the percentage of patients with uncontrolled asthma, the number of emergency department visits, the number of hospitalisations and lung function, in addition to significant decreases in ICS dose, oral corticosteroid use and antibiotics for upper respiratory tract disease [64]. Both studies were well designed, with results consistent with those from randomised clinical trials of tiotropium in asthma.…”
Section: Tiotropium Add-on Therapy Delivered Via the Respimat Soft MImentioning
confidence: 98%